Solve the quadratic inequality : x^2 - 5x + 6 <= 0

### 1 Answer | Add Yours

The inequality x^2 - 5x + 6 `<=` 0 has to be solved.

x^2 - 5x + 6 `<=` 0

=> x^2 - 3x - 2x + 6 `<=` 0

=> x(x - 3) - 2(x - 3) `<=` 0

=> (x - 2)(x - 3) `<=` 0

This is true in two case:

- x - 2 `<=` 0 and x - 3 `>=` 0

=> x `<=` 2 and x `>=` 3

This is not possible.

- x - 2 `>=` 0 and x - 3 `<=` 0

=> x `>=` 2 and x `<=` 3

This is true for x lying in [2, 3]

**The solution of the inequality is [2, 3]**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes